Endoplasmic Reticulum Stress Mediated MDRV p10.8 Protein-Induced Cell Cycle Arrest and Apoptosis Through the PERK/eIF2α Pathway - Wang, Quanxi; Yuan, Xiaoqin; Chen, Yuan; Zheng, Qingli; Xu, Lihui; Wu, Yijian (Frontiers in Microbiology, 2018)
In this study, the mechanism of Muscovy duck reovirus (MDRV) p10.8 protein-induced pathogenesis was investigated, with a focus on endoplasmic reticulum (ER) stress. In chicken embryo fibroblasts cell lines (DF1), pCI-neo-flg-p10.8 protein transfection increased the phosphorylation (p-) levels of PERK and eIF2α as shown by Western blotting analysis and led to the dissociation of BiP from PERK as shown by co-immunoprecipitation (Co-IP) analysis. Results of treatment with both ER stress activator and inhibitor further confirmed that p10.8 protein induced ER stress. Subsequently, using flow cytometry analysis, it was also found that p10.8 protein induced cell cycle arrest during the G0／G1 phase. Furthermore, p10.8 transfection increased the phosphorylation levels of PERK and eIF2α, and reduced the expression levels of CDK2, CDK4, and Cyclin E according to Western blotting analysis. Treatment with ER stress activator and ER stress inhibitor after p10.8 protein transfection in DF1 cells further indicated that p10.8 protein induced ER stress, which resulted in cell cycle arrest. The results of knockdown of either PERK or eIF2α genes further confirmed that p10.8 protein-induced ER stress led to cell cycle arrest through the PERK/eIF2α pathway. Further results showed that p10.8 protein induced ER stress and apoptosis in DF1 cells. The expression levels of p-PERK, p-eIF2α, CHOP, cleaved-Caspase12, and cleaved-Caspase3 were increased by p10.8 protein. Test results of treatment with each of Tunicamycin, TUDCA and knockdown of PERK, and eIF2α, confirmed that p10.8 protein induced ER stress involving apoptosis via the PERK/eIF2α pathway. In conclusion, MDRV p10.8 protein induced ER stress that caused cell cycle arrest and apoptosis through the PERK/eIF2α pathway.